Hubungan Tingkat Pengetahuan dengan Kepatuhan Terapi ARV pada ODHA di Yogyakarta - Erika Agustin Wulandari; Dwi Kartika Rukmi (PSIK FKKMK UGM, 2021)
Background: Knowledge is something that can influence individual behaviour, and it is also one of the factors that can affect adherence. On the other hand, an individual who has knowledge about HIV/AIDS does not always has good adherence to ARV (antiretroviral) therapy.Objective: Determine the correlation between the level of HIV/AIDS knowledge with the adherence to ARV therapy in people living with AIDS (PLWHA) at the Victory Plus Foundation, Yogyakarta.Methods: This research was a correlative analytic study with a cross-sectional design approach. A total of 67 PLWHA who underwent ARV therapy at the Victory Plus Foundation Yogyakarta were chosen as respondents through purposive sampling technique, between May and July 2019. Data collection used the HIV/AIDS Knowledge Level Questionnaire and The Morisky Medication Adherence Scale (MMAS-8), which have been considered as valid and reliable. Somers' D Test used to analyze obtained data.Results: The level of knowledge of PLWHA in this study was in the high category (92,5%), while adherence to ARV therapy was in the moderate category (40,3%). There is no significant correlation between the level of knowledge and adherence to ARV therapy (r= 0,113; p-value= 0,153).Conclusion: The level of knowledge of HIV patients undergoing ARV therapy at the Victory Plus Foundation Yogyakarta is high and their adherence to ARV therapy is moderate, but there is no relationship between these two variables. Consequently, healthcare provider should focus on other scientific-proven factors, than HIV/AIDS knowledge, to increase ARV therapy adherence among patients for successful HIV treatment. ABSTRAKLatar Belakang: Pengetahuan merupakan salah satu faktor yang dapat memengaruhi perilaku individu dan kepatuhan. Namun, individu yang memiliki pengetahuan yang baik tentang HIV/AIDS tidak selalu memiliki kepatuhan terapi ARV (antiretroviral) yang baik.Tujuan: Mengetahui hubungan tingkat pengetahuan HIV/AIDS dengan kepatuhan terapi ARV pada orang dengan HIV AIDS (ODHA) di Yayasan Victory Plus Yogyakarta.Metode: Penelitian ini merupakan penelitian analitik korelatif dengan pendekatan desain cross sectional. Sebanyak 67 ODHA yang menjalani terapi ARV di Yayasan Victory Plus Yogyakarta dipilih sebagai responden dengan teknik purposive sampling, antara bulan Mei hingga Juli 2019. Pengumpulan data menggunakan kuesioner Tingkat Pengetahuan HIV/AIDS dan Morisky Medication Adherence Scale (MMAS-8), yang sudah valid dan reliabel. Uji Somers' D digunakan untuk menganalisis data yang diperoleh.Hasil: Tingkat pengetahuan ODHA dalam penelitian ini termasuk dalam kategori tinggi (92,5%), sedangkan kepatuhan terapi ARV dalam kategori sedang (40,3%). Tidak ada hubungan yang signifikan antara tingkat pengetahuan dengan kepatuhan terapi ARV (r= 0,113; p-value= 0,153).Kesimpulan: Tingkat pengetahuan pasien HIV yang menjalani terapi ARV di Yayasan Victory Plus Yogyakarta tinggi dan kepatuhan terapi ARV sedang, tetapi tidak ada hubungan antara kedua variabel tersebut. Dampaknya, penyedia layanan kesehatan harus fokus pada faktor-faktor ilmiah lain, selain pengetahuan HIV/AIDS, agar dapat meningkatkan kepatuhan terapi ARV di antara pasien untuk pengobatan HIV yang berhasil.